Encyclopedia of marine biotechnology - Kim, Se-Kwon (Wiley-Blackwell, 2020)
"This encyclopedia presents comprehensive content of topics in marine biotechnology -- all in one place for the first time, of use to both novices and experts. The reference starts with the history and an overview of marine biotechnology, followed by information on marine organisms, bioprocess techniques, marine natural products, biomaterials, bioenergy and algal biotechnology. It also covers marine food and biotechnology applications in areas such as pharmaceuticals, cosmeceuticals and nutraceuticals. Each topic covered also shows detailed information on 10-30 subtopics. The United States is the world leader in marine biotechnology (representing the single largest region for marine biotechnology worldwide); however, research activities are growing in Brazil, Canada, China, Japan, Republic of Korea and Australia. This encyclopedia will have a vast audience including students as well as industrialists - many upcoming universities are bringing up this subject to graduate as well as postgraduate level. The author is well known internationally in the field. 100 contributors from Asia, USA, South America, South Africa, Europe and the UK, lend their vast knowledge to the five-volume set. Other marine biotechnology books on the market are outdated and cover only the industrial applications of marine biotechnologies. Most of these books miss out bioenergy generation: an important topic today as most energy sources are non-renewable and it is a major area of expansion in marine biotechnology"--